Minimization of the performance degradation of laser parameters with operating time of quantum dot laser using indium nitride - Humayun, M.A.; Rashid, M.A.; Malek, F.; Namihira, Y. (Physics Essays Publication, 2015)
We have analyzed theoretically the effect of laser operating time on feedback characteristics of quantum dot laser using GaN, AIN, and inN as the active layer material. Our Investigation includes features like carrier density, feedback strength, and Fermi wave function of quantum dot laser. The laser operating time of quantum dot laser affects the carrier concentration, fermi wave function, and feedback strength. As carrier concentration has been improved by using InN as the active material, the other parameters related to it have also been improved. The other parameter improvements have been achieved in terms of improved feedback strength higher Fermi wave function.